PENGARUH KEPUASAN KONSUMEN, SWITCHING BARRIERS DAN PENANGANAN KELUHAN TERHADAP LOYALITAS KONSUMEN PAMELA SWALAYAN SUPERMARKET - Maria Kumalasanti (Solusi: Jurnal Kajian Ekonomi dan Bisnis, 2012)
Assumption from this research reflected in hypothesis that suspect that there is a positive and significant influence from customer satisfaction, barriers switching, complaints handling to customer loyalty Pamela supermarket. For testing the validity from that hypothesis it’s needed a related from worker opinion about customer satisfaction, barriers switching, complaints handling and customer loyalty Pamella Supermarket. Data explored based on judgment and customers opinion from 60 respondents. The result of regression analysis is meanwhile F is 80,400 with significant 0,00 , R is 0,812. So the variable can explained 81,2% to customer loyalty and the rest 18,8 % can explained another variables. From the research it can be concluded customer satisfaction, barriers switching, and complaints handling have positive influence to customer loyalty.